1999
DOI: 10.1037/0022-3514.76.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in autobiographical memory for childhood emotional experiences.

Abstract: Research to date has paid remarkably little heed to gender differences in autobiographical memory. To redress this, the author examined memory for childhood events in adult men and women remembering back to childhood, and in children themselves. Five studies were conducted, and results revealed that females consistently recalled more childhood memories than males did and were generally faster in accessing the memories recalled. Furthermore, the gender difference observed was specific to memories of events asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
171
7
14

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(212 citation statements)
references
References 49 publications
20
171
7
14
Order By: Relevance
“…Previous studies have shown that women typically recall more emotional information than men (Bloise & Johnson, 2007;Davis, 1999;Fujita et al, 1991;Seidlitz & Diener, 1998). The present findings show that, under some conditions, women's memory for negative emotional information may be less accurate than that of men.…”
Section: Discussionmentioning
confidence: 34%
See 1 more Smart Citation
“…Previous studies have shown that women typically recall more emotional information than men (Bloise & Johnson, 2007;Davis, 1999;Fujita et al, 1991;Seidlitz & Diener, 1998). The present findings show that, under some conditions, women's memory for negative emotional information may be less accurate than that of men.…”
Section: Discussionmentioning
confidence: 34%
“…For example, Davis (1999) found that women recalled more emotional childhood memories than men and recalled them more rapidly than men. Similarly, both Fujita, Diener, and Sandvik (1991) and Seidlitz and Diener (1998) found that women recalled more positive and negative autobiographical memories than men in timed retrieval tasks.…”
mentioning
confidence: 99%
“…First, the gender distribution is quite uneven. Indeed, research has shown that females have more detailed and emotionally intense autobiographical memories than men (Davis, 1999;Fujita, Diener, & Sandvik, 1991). Second, the N of the study is a bit small, though the statistical analysis shows that it is large enough to obtain significant results.…”
Section: General Conclusionmentioning
confidence: 96%
“…In adults, research has shown that on word cueing tasks, where participants are required to generate specific memories to cues, males are more likely to offer generalised memories (i.e., summaries of events) (Goddard, Dritschel & Burton, 1998). Compared with females, males also report less detailed, vivid, and emotional memories (Pillemer, Wink, DiDonato & Sanborn, 2003), fewer relationally oriented narratives (Buckner & Fivush, 2000) and they report fewer childhood memories and are slower to access them (Davis, 1999). Given the very small number of females generally included in autism studies the question arises as to whether autobiographical memory deficits are as prevalent among females with ASD as among males, or whether their retrieval style is more in line with females without ASD.…”
mentioning
confidence: 99%